Hubungan Kepatuhan Konsumsi Kalsium Karbonat terhadap Kadar Fosfat Pasien Gagal Ginjal dengan Hemodialisis - Fika Nuzul Ramadhani (Journal Syifa Sciences and Clinical Research, 2023)
Non-adherence to renal failure treatment increases the risk of disease complications, such as metabolic disorders of calcium and phosphate. Education is one of way to increase medication adherence. Education is one way to increase patient compliance in therapy. One way of conducting education is by giving leaflets. This study aims to determine the correlation between compliance with consumption of calcium carbonate and phosphate levels in patients with kidney failure on hemodialysis. This research were experimental and prospective study at PKU Muhammadiyah General Hospital, Yogyakarta City for 4 weeks using the one-group pretest posttest design to test patients' phosphate levels pre and post administation of leaflets increase adherence. Sample consisted of 70 kidney disease patients with hemodialysis were divided into 2 groups, each consisting of 35 patients. The intervention group were given education leaflets and checking phosphate levels, while the control group were not given leaflets. Data were obtained from medical records, questionnaire instruments and phosphate laboratory data. The level of patient adherence in taking calcium carbonate medication assessed by MMAS questionnaire and phosphate levels of patients. Data were analysis using the Wilcoxon test and Spearman test.The results of the analysis between adherence and phosphate levels showed no relationship between adherence and phosphate levels p=0.591 (p0.05). Overall, it can be concluded that there is no correlation between adherence to calcium carbonate consumption and phosphate levels